Allele frequencies of CSF1 PO, TPOX and TH01 STRs in random Chinese population of Malaysia - Swaran, Yuvaneswari D/0 Chandramoulee (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2004)
Allele and genotype distribution pattern for three tetrameric short tandem repeat (S1R) loci were established from 100 unrelated ethnic Chinese population of Malaysia using polymerase chain reaction (PCR), followed by electrophoresis of the PCR products in denaturing polyacrylamide gels and subsequent detection by silver staining. The STR loci are CSFIPO, TPOX, and THOl. This study was done to evaluate their significance in human identification and population genetics study for forensic casework analysis. The observed genotypic distribution showed no significant deviation from Hardy-Weinberg equilibrium (P>0.05). The data in this study have been compared with other published population data. 1